P-041 Impact of a Patient Support Program on Resource Costs in Inflammatory Bowel Disease. (March 2016) - Rubin, David; Skup, Martha; Davis, Matthew; Johnson, Scott; Chao, Jingdong
Abstract : Background: AbbVie provides a free-to-patient Patient Support Program (PSP) to adalimumab (ADA)-treated patients to assist them with issues pertaining to medication costs, nurse support, injection training, pen disposal, and medication reminders. 1 Use of these resources has been found to reduce healthcare costs in a cross-indication analysis 2 ; however, the benefits of the PSP specifically for patients with inflammatory bowel disease (IBD) have not been studied. We aimed to quantify the relationship between participation in any component of the PSP and resource costs (medical and total) among patients with IBD. Methods: Longitudinal patient-level data on the use of AbbVie's PSP were linked with Source Healthcare Analytics administrative claims data for patients initiating ADA treatment from 01/2008 to 10/2014. The primary sample included patients aged ≥18 years with a diagnosis of IBD (i.e., Crohn's disease or ulcerative colitis) who were anti-tumor necrosis factor–naive prior to initiation of ADA. Patients who enrolled in the PSP (PSP cohort) were matched to those who did not enroll (non-PSP cohort) based on age, sex, year of treatment initiation, comorbidities, diagnosis, and initiation at a specialty pharmacy. For the PSP cohort, the index date was assigned as the date of enrollment into the PSP program, and their time to enrollment following initiation was used to assign index dates for the non-PSP cohort. All patients were required to have evidence of medical and pharmacy coverage for 6 months before/after their first ADA claim and for 6 months after the index date. Medical costs associated with emergency department, inpatient, physician, and outpatient visits (all-cause and disease-related) and total costs (medical costs plus drug costs) were compared at 6 months following the index date using t tests and generalized linear models adjusting for key baseline variables. Patients with costs >5 times the standard deviation above the mean were excluded as outliers (13 for PSP, 29 for non-PSP). Results: A total of 500 PSP patients and 484 non-PSP patients were included. Baseline characteristics were similar between cohorts. During the follow-up period, unadjusted analyses showed that PSP patients had significantly lower 6-month medical costs (excluding charges for study drugs) than non-PSP patients by 32% (11, 866 versus 17, 374; P = 0.0044). Disease-related medical costs were 28% lower for PSP patients compared with non-PSP patients (6484 versus 9067; P = 0.0498). Total costs were 18% lower for PSP patients than non-PSP patients (24, 773 versus 30, 097; P = 0.0085). Adjusted analyses yielded similar findings. Conclusions: Enrollment in AbbVie's PSP was associated with reduced medical costs (all-cause and disease-related) and total healthcare costs for patients with IBD. Further analysis will explore the specific elements of this program that might benefit all patients with IBD, regardless of therapy.